PENGARUH DOPING MANGAN TERHADAP KOMPOSISI DAN SIFAT KRISTALINITAS PARTIKEL OKSIDA BESI PASIR ALAM SUNGAI ROKAN DIPREPARASI DENGAN METODE BALL MILLING - Rahman Kurniawan; Salomo Salomo; Erwin Erwin; Defrianto Defrianto (Universitas Riau, 2022)
The composition, crystallinity and magnetic susceptibility of nanoparticles in natural sand of the Rokan River, Riau Province have been investigated. After the iron sand separator (ISS) process, the natural sand samples were separated using NdFeB magnets to separate iron oxide particles and other non-ferrous oxides. For 70 hours, the NdFeB product was prepared using the ball milling method to produce BM products. The BM products were ball milled for 30 hours with a manganese doping concentration of 0 wt.%; 5 wt.%, and 10 wt.% produced DM 0, DM 5 and DM 10 products. Magnetic susceptibility values increased based on the values of B0 and BT measured using Pasco Magnetic Probe PS-2162. The results of XRD analysis of DM products contain a hematite phase (α-Fe2O3) which has a hexagonal structure. The crystal size increased along with the increasing concentration of Manganese from 25.494 nm; 25,542 nm to 25.669 nm. The results of XRF analysis of DM products on Fe elements decreased in percentage with increasing Manganese concentration from 18.083%; 15.407% to 12.947%. Other chemical elements such as Si, Al, K, P, Ti, Ca, Ti, Cr, Zn, V and Pb also decreased.